2013
DOI: 10.1002/ccd.25087
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of abluminal biodegradable polymer biolimus‐eluting stents and durable polymer everolimus‐eluting stents in the treatment of coronary bifurcations

Abstract: BES use in the treatment of bifurcation lesions appears to be associated with good clinical outcomes, comparable to those seen with EES, at long-term follow-up. These results are hypothesis-generating and need to be validated with larger studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…In the BiOSS ® stent biodegradable polymer is applied, so the crucial matter is its stability and time of degradation. However, in other reports it was shown that the type of the polymer (biodegradable vs. durable) did not play a significant role in coronary bifurcation treatment [28].…”
Section: Discussionmentioning
confidence: 82%
“…In the BiOSS ® stent biodegradable polymer is applied, so the crucial matter is its stability and time of degradation. However, in other reports it was shown that the type of the polymer (biodegradable vs. durable) did not play a significant role in coronary bifurcation treatment [28].…”
Section: Discussionmentioning
confidence: 82%
“…In BiOSS® stent, the polymer is biodegradable, so crucial matter is its stability and time of degradation. However, in other papers, it was shown that the type of polymer (biodegradable vs durable) did not play a significant role in coronary bifurcation treatment …”
Section: Discussionmentioning
confidence: 89%
“…Currently, there are limited data regarding the clinical outcome of DES with biodegradable polymers used for stenting of bifurcation lesions . Our study clearly reinforces preliminary observations showing favorable intermediate‐term and long‐term outcomes, with a low rate of TLF and stent thrombosis following bifurcation stenting.…”
Section: Discussionmentioning
confidence: 94%